Diseño, implementación y monitoreo de un prototipo de robot sembrador de trigo - Contreras Calcetero, Harold Johann; Cañón Faustino, Andrés Felipe (Universidad Antonio Nariño, 2022)
In the following work, the design of a robot dedicated to the sowing of wheat will be developed through different simulation tools and programming languages that will allow to model this type of systems in a simpler way, allowing to know the behavior of the robot before any type of physical implementation, however this work will focus on the calculations necessary for the design of the robot mechanisms and also a navigation system through a PID controller which will be implemented at the time of building the robot. The work will be divided into two fundamental parts that are: mechanics and electronics In the first place, the mechanical design will be carried out that will allow the robot to perform its motor functions based on its dimensions, manufacturing materials, robot shape, manufacturing technology, among characteristics which must be taken into account during the construction of the robot, of In the same way, a navigation system will be designed that will allow the robot to have autonomy in any type of terrain that is presented to it when executing its sowing tasks such as obstacle detection, speed control and path tracking, among others. Finally, at the time of calculating and designing the aforementioned, both parts are integrated, both mechanics and electronics, to carry out experimental tests in a planting site in order to evaluate its optimal operation.